2017
DOI: 10.4172/2155-9597.1000321
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Biofilm Forming Ability of Bacterial Isolates from Contact Lenses and their Accessories

Abstract: In modern era the usage of contact lens is increased in youngsters especially in females with a high risk of ocular infections. In current research bacteriological analysis and bio-film forming ability of 22 contact lens accessories samples (Contact lenses, contact lens storage kit and contact lens solution) is studied. The isolated bacteria includes Corynebacterium spp, S. aureus, coagulase negative Staphylococcus, Bacillus spp. and Streptococcus spp. Bio-film are the main cause of bacterial infection. The bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Since all the three isolates originated from the (controlled) biofouling model, this signifies that biofilm formation could depend strongly on environmental conditions such as availability of nutrients, moisture and temperature. The result of Zuberi and Nadeem (2017) corroborates the finding of this study as they similarly reported as high as 63.64% biofilm formation in bacteria isolated from contact lenses and their accessories in Karachi, Pakistan.…”
Section: Resultssupporting
confidence: 91%
“…Since all the three isolates originated from the (controlled) biofouling model, this signifies that biofilm formation could depend strongly on environmental conditions such as availability of nutrients, moisture and temperature. The result of Zuberi and Nadeem (2017) corroborates the finding of this study as they similarly reported as high as 63.64% biofilm formation in bacteria isolated from contact lenses and their accessories in Karachi, Pakistan.…”
Section: Resultssupporting
confidence: 91%
“…Zuberi* and Nadeem [42] reported in their study when compared this method in compare with other results the CRA plate method for detecting biofilm production, reported that only four isolates produced black crystalline morphology, while 111 showed orange colonies…”
Section: Congo Red Results For S Enterica Serovar Typhi Figure (2)mentioning
confidence: 91%
“…The biofilm forming ability of these bacterial isolates is studied by CRA method and tube method. Best results were observed by TM [10].…”
Section: Discussionmentioning
confidence: 93%
“…A total of 298 CLs samples were collected with sterile cotton swab moistened with sterile normal saline solution [10], then delivered with proper transport media to the medical microbiology department at Faculty of Medicine and Health Science, University of Science and Technology and processed.…”
Section: Samples Collectionmentioning
confidence: 99%